Small Myristoylated Protein-3, Identified as a Potential Virulence Factor in Leishmania amazonensis, Proves to be a Protective Antigen against Visceral Leishmaniasis - Oliveira, Marcelo; Martins, Vívian; Santos, Thaís; Lage, Daniela; Ramos, Fernanda; Salles, Beatriz; Costa, Lourena; Dias, Daniel; Ribeiro, Patrícia; Schneider, Mônica; Machado-de-Ávila, Ricardo; Teixeira, Antônio; et al. (International journal of molecular sciences, 2018)
In a proteomics approach conducted with Leishmania amazonensis, parasite proteins showed either an increase or a decrease in their expression content during extensive in vitro cultivation, and were related to the survival and the infectivity of the parasites, respectively. In the current study, a computational screening was performed to predict virulence factors among these molecules. Three proteins were selected, one of which presented no homology to human proteins. This candidate, namely small myristoylated protein-3 (SMP-3), was cloned, and its recombinant version (rSMP-3) was used to stimulate peripheral blood mononuclear cells (PBMCs) from healthy subjects living in an endemic area of leishmaniasis and from visceral leishmaniasis patients. Results showed high interferon-γ (IFN-γ) production and low levels of interleukin 10 (IL-10) in the cell supernatants. An in vivo experiment was then conducted on BALB/c mice, which were immunized with rSMP-3/saponin and later challenged with Leishmania infantum promastigotes. The rSMP-3/saponin combination induced high production of protein-specific IFN-γ, IL-12, and granulocyte-macrophage colony-stimulating factor (GM-CSF) by the spleen cells of the immunized mice. This pattern was associated with protection, which was characterized by a significant reduction in the parasite load in distinct organs of the animals. Altogether, these results have revealed that this new virulence factor is immunogenic in both mice and humans, and have proven its protective efficacy against visceral leishmaniasis in a murine model.